Synthesis of Magnetic Iron Oxide-Incorporated Cellulose Composite Particles: An Investigation on Antioxidant Properties and Drug Delivery Applications - Arifa Naznin; Palash Kumar Dhar; Sagar Kumar Dutta; Sumon Chakrabarty; Utpal Kumar Karmakar; Pritam Kundu; Muhammad Sarwar Hossain; Hasi Rani Barai; Md. Rezaul Haque (MDPI AG, 2023)
In recent years, polymer-supported magnetic iron oxide nanoparticles (MIO-NPs) have gained a lot of attention in biomedical and healthcare applications due to their unique magnetic properties, low toxicity, cost-effectiveness, biocompatibility, and biodegradability. In this study, waste tissue papers (WTP) and sugarcane bagasse (SCB) were utilized to prepare magnetic iron oxide (MIO)-incorporated WTP/MIO and SCB/MIO nanocomposite particles (NCPs) based on in situ co-precipitation methods, and they were characterized using advanced spectroscopic techniques. In addition, their anti-oxidant and drug-delivery properties were investigated. Field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD) analyses revealed that the shapes of the MIO-NPs, SCB/MIO-NCPs, and WTP/MIO-NCPs were agglomerated and irregularly spherical with a crystallite size of 12.38 nm, 10.85 nm, and 11.47 nm, respectively. Vibrational sample magnetometry (VSM) analysis showed that both the NPs and the NCPs were paramagnetic. The free radical scavenging assay ascertained that the WTP/MIO-NCPs, SCB/MIO-NCPs, and MIO-NPs exhibited almost negligible antioxidant activity in comparison to ascorbic acid. The swelling capacities of the SCB/MIO-NCPs and WTP/MIO-NCPs were 155.0% and 159.5%, respectively, which were much higher than the swelling efficiencies of cellulose-SCB (58.3%) and cellulose-WTP (61.6%). The order of metronidazole drug loading after 3 days was: cellulose-SCB < cellulose-WTP < MIO-NPs < SCB/MIO-NCPs < WTP/MIO-NCPs, whereas the sequence of the drug-releasing rate after 240 min was: WTP/MIO-NCPs < SCB/MIO-NCPs < MIO-NPs < cellulose-WTP < cellulose-SCB. Overall, the results of this study showed that the incorporation of MIO-NPs in the cellulose matrix increased the swelling capacity, drug-loading capacity, and drug-releasing time. Therefore, cellulose/MIO-NCPs obtained from waste materials such as SCB and WTP can be used as a potential vehicle for medical applications, especially in a metronidazole drug delivery system.